Corrections of HPGe detector efficiency curve due to true coincidence summing by program EFFTRAN and by Monte Carlo simulations. (November 2022) - Knezevic, J.; Mrdja, D.; Hansman, J.; Bikit, K.; Forkapic, S.; Bikit, I.; Velimirovic, D.; Kuzmanovic, P.
Abstract: Standard reference sources, used for efficiency curve calibration of detector, often contain radionuclides with complex decay schemes (such as 60 Co, 88 Y, 152 Eu …), introducing a potential problem in gamma-ray spectrometry, due to the appearance of coincidence summing of detected photons, in particular at a low source-detector distance. In this paper, a set of Monte Carlo simulations of an identical experimental setup were performed in order to obtain the efficiency curve of coaxial p-type HPGe detector for energy region (0–2) MeV, with the effect of true coincidence summing and without it. Obtained efficiency curves are compared with the experimental curve after applied EFFTRAN corrections. Fairly well agreement (between simulated and experimental curves with EFFTRAN corrections (with a relative deviation of 10%) proved the reliability of EFFTRAN corrections, as well as the possibility of Monte Carlo simulations for efficiency curve determination. Highlights: A set of Monte Carlo simulations were performed to obtain an HPGe efficiency curve . The true coincidence summing effect was investigated . Efficiency curves are compared with experimental after applied EFFTRAN corrections . Well agreement proved the reliability of EFFTRAN corrections . The use of Monte Carlo simulations for efficiency curve determination was verified .